Identification of novel esterase-active enzymes from hot environments by use of the host bacterium Thermus thermophilus - Leis, Benedikt; Angelov, Angel; Mientus, Markus; Li, Haijuan; Pham, Vu T. T.; Lauinger, Benjamin; Bongen, Patrick; Pietruszka, Jörg; Gonçalves, Luís G.; Santos, Helena; Liebl, Wolfgang (Frontiers in Microbiology, 2015)
Functional metagenomic screening strategies, which are independent of known sequence information, can lead to the identification of truly novel genes and enzymes. Since E. coli has been used exhaustively for this purpose as a host, it is important to establish alternative expression hosts and to use them for functional metagenomic screening for new enzymes. In this study we show that Thermus thermophilus HB27 is an excellent screening host and can be used as an alternative provider of truly novel biocatalysts. In a previous study we constructed the mutant strain BL03 that was no longer able to grow on defined minimal medium supplemented with tributyrin as the sole carbon source and could be used as a host to screen for metagenomic DNA fragments that could complement growth on tributyrin. Several thousand single fosmid clones from thermophilic metagenomic libraries from heated compost and hot spring water samples were subjected to a comparative screening for esterase activity in both T. thermophilus strain BL03 and E. coli EPI300. We scored a greater number of active clones in the thermophilic bacterium than in the mesophilic E. coli. From all clones functionally screened in E. coli, only two thermostable α/β-fold hydrolase enzymes with high amino acid sequence similarity to already characterized enzymes were identifiable. In contrast, five further fosmids were found that conferred lipolytic activities in T. thermophilus. Four open reading frames (ORFs) were found which did not share significant similarity to known esterase enzymes. Two of the genes were expressed in both hosts and the novel thermophilic esterases, which based on their primary structures could not be assigned to known esterase or lipase families, were purified and preliminarily characterized. Our work underscores the benefit of using additional screening hosts other than E. coli for the identification of novel biocatalysts with industrial relevance.